Reasons for the schools violence among the secondary stage students in the directorate of education of southern Al-Shooneh District from the point of view - Al-Amareen, Mokhled (DIRASAT: EDUCATIONAL SCIENCES, 2016)
This study aimed to know the reasons for the school’s violence among the secondary stage students in the directorate from the point of view of the schools principals, in the scholastics year 2015-2016. The researcher used the descriptive method with its procedures and steps, because of its relevance to the nature of the study. Study sample population consisted of (18) male and female principals were purposely selected. To achieve the study goal, the researcher prepared on instrument for that purpose, represents by a questionnaire which consisted of (36) clauses distributed to three reasons to measure the violence (social, schools, and psychological reasons). The results showed that the social reasons have the great role in the schools violence with the mean (2.40) and standard deviation (2.24), white the schools reasons came in the second place with the mean (2.30), and standard deviation (0.29) and the psychological reasons came in the last rank with the mean (2.27) and standard deviation (0.38). In the light of these results, the researcher recommending the schools administrations should care about the students social issues inside their schools and the work to survey the students social position to deal with the student through understanding his social background and activating the social partnership between the school and the society.